International Accounting and Reporting Issues - 2019 Review - United Nations Conference on Trade; Development (United Nations, 2021)
This publication presents findings of surveys of implementation of the Guidance on Core Indicators for Entity Reporting on Contribution towards Implementation of the Sustainable Development Goals (GCI) conducted on the Dow 30 companies in the USA and the 30 companies that form the index of the Egyptian Stock Exchange. It further contains a review of recent developments in international standards of accounting and reporting in the public and private sectors.